Diversity and geographic distribution of haplotypes of Dirofilaria immitis across European endemic countries - Alsarraf, Mustafa; Carretón, Elena; Ciuca, Lavinia; Diakou, Anastasia; Dwużnik-Szarek, Dorota; Fuehrer, Hans-Peter; Genchi, Marco; Ionică, Angela Monica; Kloch, Agnieszka; Kramer, Laura Helen; Mihalca, Andrei D; Miterpáková, Martina; et al. (Parasites & Vectors, 2023)
Background: Dirofilaria immitis, also known as heartworm, is one of the most important parasitic nematodes of domestic dogs, causing a potentially serious disease, cardiopulmonary dirofilariosis, which can be lethal. This species seems to be less 'expansive' than its sister species Dirofilaria repens, and it is believed that climate change facilitates the spread of this parasite to new non-endemic regions. Methods: In total, 122 heartworm isolates were analysed from nine endemic countries in Europe (Portugal, Spain, Italy, Greece, Hungary, Romania, Slovakia, and Ukraine) and a single isolate from Bangladesh by amplification and sequencing of two mitochondrial (mt) DNA markers: cytochrome c oxidase subunit 1 (COI) and dehydrogenase subunit 1 (NADH). The main aim of the current study was to determine the genetic diversity of D. immitis and compare it with D. repens haplotype diversity and distribution. DNA was extracted from adult heartworms or microfilariae in blood. Most isolates originated from dogs (Canis lupus familiaris) while 10 isolates originated from wildlife species from Romania, including eight isolates from golden jackals (Canis aureus), one isolate from a Eurasian otter (Lutra lutra) and one isolate from a red fox (Vulpes vulpes). Results: Median spanning network analysis was based on the combined sequence (1721 bp) obtained from two mt markers and successfully delineated nine haplotypes (Di1-Di9). Haplotype Di1 was the dominant haplotype encompassing 91 out of the 122 sequences (75%) from all nine countries and four host species. Haplotype Di2 was the second most common haplotype, formed solely by 13 isolates from Italy. The remaining sequences were assigned to Di3-Di9 haplotypes, differing by 1-4 SNPs from the dominant Di1 haplotype. There was evidence for geographical segregation of haplotypes, with three unique haplotypes associated with Italy and four others associated with certain countries (Di4 and Di7 with Slovakia; Di8 with Greece; Di6 with Hungary). Conclusion: Diversity in D. immitis mt ...